Age‐related intestinal monosaccharides transporters expression and villus surface area increase in broiler and layer chickens. Issue 1 (26th September 2019) - Li, Huifeng; Cheng, Jin; Yuan, Yitong; Luo, Rong; Zhu, Zhiwei
Abstract: In the chicken small intestine, glucose is mainly transported by the apically located sodium/glucose cotransporter 1 ( SGLT1 ) and the basolaterally located glucose transporter 2 ( GLUT2 ). Fructose is transported by the apically located glucose transporter 5 ( GLUT5 ) and similarly by GLUT2 . During the early post‐hatching period, the intestinal villus surface area (VSA) should be considered as an important factor related to the monosaccharide absorption capacity. Our objective here was to study intestinal monosaccharide absorption by analyzing the effects of age, diet, and breed on monosaccharide transporters and the VSA. The mRNA expression patterns of SGLT1, GLUT2 and GLUT5 genes in broiler and layer chickens were measured from the day of hatching to day 28 using the absolute quantitative real‐time PCR. Both the intestinal mRNA expression levels of these genes and the VSA were affected by age. The mRNA expression levels of SGLT1 and GLUT2 were significantly increased from day 1 to day 3 and then decreased from day 3 to day 28. The expression levels of GLUT5 decreased from day 1 to day 7. The broiler chickens VSAs were significantly larger than those of the layer chickens from days 7 to 28. The effect of diet on the gene expression patterns of these monosaccharide transporters and the VSA were not significant. Our results suggest that the expression levels of these monosaccharide transporters are increased rapidly at the beginning of intestinal growth to meet the demands for monosaccharides to support the fast growth of the chick before day 7. As intestinal maturation and VSA increased, the expression levels of these monosaccharide genes decreased to a certain expression level to maintain the intestinal transport capacity and the absorption balance of all other nutrients.